Does Bilateral Trust Matter During Mergers and Acquisitions Negotiations? - Muhammad Farooq Ahmad; Nihat Aktas; Saqib Aziz (British Journal of Management, 2022)
We examine the effect of bilateral trust on cross-border mergers and acquisitions (M&As). Using a large European M&A sample, we find that bilateral trust facilitates deal announcement and completion. Bidder and target bilateral trusts towards each other are both important for deal announcement, but only bidder trust towards the target firm matters for deal completion. The effect of bilateral trust on deal completion is amplified in more complex transactions and when bidders face severe liability of foreignness. Moreover, bilateral trust between the parties is also associated positively with merger performance. These results support the importance of bilateral trust as a deal facilitator in negotiation settings characterized by contract incompleteness and liability of foreignness.
Keywords: 650